Studi Deskriptif: Persepsi Siswa terhadap Pendidikan Karakter Berbasis Nilai Budaya di SMA Negeri 3 Kediri - Isnanda, Hafiski Luthfinuddin; Ristiawan, Hendri; Ananta Sasono, Satria (Cahaya Smart Nusantara, 2025)
This descriptive study explores students' perceptions of character education based on cultural values at SMA Negeri 3 Kediri. Using a quantitative descriptive approach with a purposive sampling method, 103 students from selected classes participated by completing a Likert-scale questionnaire measuring five cultural values: cooperation (gotong-royong), politeness, hard work, tolerance, and honesty. Results indicate that students generally have positive perceptions toward the integration of cultural values into character education, with honesty receiving the highest approval rating. Despite the overall positive reception, variations in students' understanding and application of these values suggest that continuous, holistic reinforcement is needed. The findings highlight the importance of adapting character education strategies to the local cultural context to enhance students' moral and social development.